2019
DOI: 10.3390/clockssleep1030030
|View full text |Cite
|
Sign up to set email alerts
|

Napping Behaviors and Extracurricular Club Activities in Japanese High School Students: Associations with Daytime Sleep Problems

Abstract: Although engaging in evening naps and extracurricular activities are popular among Japanese high school students, the associations between these behaviors and daytime sleep problems were unclear. A questionnaire on daily life and sleeping habits was administered to 1314 high school students, aged between 15–17 years. The respondents were categorized by their after-school napping habits (did not nap, napped 1–2 days/week, napped ≥3 days/week), and their extracurricular activities (no activity, cultural club, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…In contrast to the present study, increased sleepiness was reported to be associated with fewer extracurricular activities in Canadian students [21]. However, consistent with the present study, students who belonged to athletic clubs and cultural clubs revealed significantly higher risks for falling asleep during classes [22]. Undesirably early morning arousal is reported to lead to impaired evening function with excessive sleepiness [23].…”
Section: Discussionsupporting
confidence: 56%
“…In contrast to the present study, increased sleepiness was reported to be associated with fewer extracurricular activities in Canadian students [21]. However, consistent with the present study, students who belonged to athletic clubs and cultural clubs revealed significantly higher risks for falling asleep during classes [22]. Undesirably early morning arousal is reported to lead to impaired evening function with excessive sleepiness [23].…”
Section: Discussionsupporting
confidence: 56%
“…Regarding the behavioral aspects presented in Table 6 and Table 7 , watching TV seemed to have no adverse influence on sleep in the present participants. The use of electronic devices such as smartphones has been suggested to be associated with sleep problems in adolescents [ 35 , 36 ]. A notable finding was that the time spent using electronic devices by the high school students was remarkably higher on weekends compared to weekdays and that in the mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The other point to be taught to high school students should be to avoid napping after returning home, which was answered by 25% of the students, who take a nap “several times a week” or “almost every day”. Although taking a short nap in the early afternoon, which is around the timing of the circadian dip, is known to have benefits such as preventing sleepiness and improving cognitive functions in the afternoon after the nap [ 37 ], napping after returning home in the late afternoon to evening has been reported to be associated with a later bedtime and daytime sleep impairments, such as excessive sleepiness [ 36 , 38 ]. The percentage in this study was relatively lower than that reported in the previous studies of Japanese adolescents [ 36 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations